Pengembangan Sistem Informasi Manajemen Penginapan & Homestay Pada Palmyra Homestay Malang - Koko Wahyu Prasetyo; Rizky Galuh Dewantara (J-INTECH ( Journal of Information and Technology), 2022)
Information technology has a vital contribution to improving performance in the hospitality industry sector. Factors that influence the increase in performance include resources optimization and improving the quality of the customer experience. Palmyra Homestay Malang has been carrying out room availability management activities manually. The efficiency of these activities can be further improved by implementing an information system application that integrates all relevant stakeholders. This research will develop a web and android-based information system application that provides several functional features such as reservation data management, room management, financial transactions, and reporting on housekeeping status. The application development method used in this study is the waterfall method which includes needs analysis, system design, program coding, program testing, and program implementation. The Blackbox Testing method is used to test applications by focusing on functionality to ensure the input and output of the application are as required. The output of this research is expected to make it easier for hotel management to carry out their business activities.